Customary-Based Restorative Justice: Philosophical Foundations and Normative Relevance in the Indonesian Criminal Justice System - Dheny Wahyudhi; Herlambang Herlambang; Elly Sudarti (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
The phenomenon of legal pluralism in Indonesia demonstrates the tension between customary justice rooted in local wisdom and the positive criminal law system dominated by retributive principles. This conflict often neglects the restorative dimension, where the resolution of criminal acts emphasizes the restoration of social relations rather than mere punishment. This research aims to uncover the philosophical foundations of customary-based restorative justice, while assessing its normative relevance in the context of national criminal justice. A normative juridical approach is applied through a philosophical examination of concepts such as social harmony in the Aristotelian tradition and the value of forgiveness in local culture, combined with an analysis of Indonesian legal norms. This study integrates customary ethical perspectives with modern principles of justice to evaluate how custom can become a more inclusive mechanism for criminal accountability. The research finds that customary restorative justice is philosophically grounded in culturally-based legal certainty and socially legitimate when aligned with constitutional principles, proportionality, and human rights. The 2023 New Criminal Code’s recognition of living law (Article 2) provides a formal basis for integrating customary mechanisms, which prioritize dialogue and reconciliation, thereby enhancing systemic effectiveness. This study contributes to legal reform by advocating for the formal inclusion of customary justice as a complementary approach that enriches Indonesia’s legal pluralism without compromising legality. The findings offer insights for developing more contextually just policies.